Digital Polarization Holography: Challenges and Opportunities † - Singh R.K. (My University, 2025)
Polarization has a profound impact on image quality and visual perception. For instance, polarization provides a new perspective on seeing an object which is otherwise obscured, low contrast or not measurable by conventional imaging methods. In this paper, we discuss a possible extension of the digital holography (DH) to the polarization domain, and the technique is referred to as digital polarization holography (DPH). The basic principle of the DPH is described and some of our recent contributions on quantitative vectorial imaging are covered. We also discuss and highlight the potential of combining speckle field illumination with DPH for high-resolution vectorial imaging. © 2023 by the author.